(untitled) (The Strategic Review for Southern Africa, 2020)
The Economic Freedom Index published by the Heritage Foundation ranks South Africa at 72nd out of 178 countries in terms of economic freedom in 2015. This index classifies South Africa as moderately free in terms of its level of economic freedom. While the country may be in the middle of the pack on the Economic Freedom Index, it is also often classified as one of the most unequal societies in the world. South Africa is often seen in the top five unequal countries globally with a high Gini-coefficient, and when using the Palma index (measuring the ratio of income share between the top 10 per cent and bottom 40 per cent), South Africa can also be classified as highly unequal. Therefore a contradiction seems to exist. While South Africa ranks as economically moderately free on one hand, the country is also regarded as one of the most unequal societies in the world, on the other hand. It is this contradiction that brings to the fore a contested ideological construction of economic freedom within its political narrative premised on a view that the promise of democracy had not delivered. This article presents a critical discourse analysis of the contested interpretations of economic freedom through the lens of securing liberation and the promise of democracy in South Africa: a promise built on the Freedom Charter’s construction of a democratic South Africa.